"All they have seen is a model for failure:" Stakeholder's perspectives on athletic talent development in American underserved communities. Issue 6 (2nd November 2022) - Book, Robert T.; Henriksen, Kristoffer; Stambulova, Natalia; Storm, Louise Kamuk
Abstract: This study explores the primary challenges faced and strategies implemented in underserved athletic talent development environments (UATDEs) in the United States and examines how developing within such environments impacts athletes once they reach the college and professional levels of sports. Thirteen stakeholders ( M = 10, F = 3), who had significant experience working with professional and youth athletes from underserved communities, participated in the study. Unstructured interviews lasting slightly over an hour ( M = 74 min) were analyzed using the principles of reflexive thematic analysis and the process uncovered two categories: shared features of school-based UATDEs in the United States and the ripple effects of trauma which were used to structure the findings. Within these two categories, primary themes were presented relating to the challenges observed and strategies implemented to overcome these obstacles in UATDEs as well as how developing within a UATDE can influence an athlete upon leaving the environment. The study found that stakeholders (i.e., administrators, coaches, etc.) who work within UATDEs must be aware of the inherent challenges that the environment creates and how to best support the athletes who require increased psychosocial developmental attention. Further, the same stakeholders also need to be supported in their work. Finally, when athletes from UATDEs leave the environment, stress-inducing traumatic events of their formative years may stay with them requiring that stakeholders at the university and professional levels provide support to those that need it as talent can suffer from trauma. Lay summary : This study explored the perceptions of stakeholders who work with athletes in or coming from American underserved communities. The consensus is that significant challenges exist for coaches working in such environments and athletes developing in these circumstances will likely carry emotional trauma with them during their life and athletic careers. Implications for practice: Applied practitioners working in UATDEs must prioritize the psychosocial development of their athletes as much, if not more, than athletic development. Organizations, such as AASP and ISSP must educate (e.g., through conferences, seminars, webinars, etc.) stakeholders and coaches working in UATDEs of the potential challenges faced and resources required to excel in such environments. Applied practitioners in university and professional sport must understand that athletes coming from UATDEs will need additional and specialized support focused upon, for example, the transition to a new environment or managing the ripple effects of trauma.